Are there new approaches for diagnosis, therapy guidance and outcome prediction of sepsis? - Kojic, Dubravka; Siegler, Benedikt Hermann; Uhle, Florian; Lichtenstern, Christoph; Nawroth, Peter Paul; Weigand, Markus A.; Hofer, Stefan; Brenner, Thorsten (World Journal of Experimental Medicine, 2015)
Are there new approaches for diagnosis, therapy guidance and outcome prediction of sepsis?
Gesehen am 15.07.2020